2020
DOI: 10.1007/s11357-020-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific muscle and metabolic biomarkers associated with gait speed and cognitive transitions in older adults: a 9-year follow-up

Abstract: Physical frailty and cognitive frailty share biological mechanisms, but sex-specific biomarkers associated with transitions in gait speed and cognition during ageing are poorly understood.Gait speed, cognition (3MSE), body composition (DXA) and serological biomarkers were assessed annually over 9 years in 216 males (72.7 + 8.07 years) and 384 females (71.1 + 8.44 years). In females, maintaining normal gait speed was associated with lower percent body fat (IRR 0.793, p = 0.001, 95%CI 0.691-0.910) and lower lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Sex‐based subgroups analysis revealed borderline significant improvement in maximal gait speed among men. Reasons for the difference in training response may lie in sex‐specific muscle and metabolic biomarkers that are associated with gait speed and cognition 38 . Even though the subgroup analyses of this study were preplanned, the number of participants in these analyses do not allow us to draw definite conclusions.…”
Section: Discussionmentioning
confidence: 89%
“…Sex‐based subgroups analysis revealed borderline significant improvement in maximal gait speed among men. Reasons for the difference in training response may lie in sex‐specific muscle and metabolic biomarkers that are associated with gait speed and cognition 38 . Even though the subgroup analyses of this study were preplanned, the number of participants in these analyses do not allow us to draw definite conclusions.…”
Section: Discussionmentioning
confidence: 89%
“…LDH levels have previously been highlighted as markers for the severity of COVID-19 ( Henry et al, 2020 ). The maintenance of normal cognition in older adults is highly correlated with low levels of LDH ( Waters et al, 2020 ). No correlation was found between oxygen saturation and cognitive dysfunction, suggesting that the deficits were not caused by brain hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high LDL levels were associated with lower risk of cognitive impairment in the oldest elderly (aged 80 and older), but not in the [53,55]. Improved cognition was associated with lower triglyceride only in males [56]. However, a recent study showed that high total serum cholesterol in later life compared to midlife was not associated with any form of dementia or cognitive decline [45].…”
Section: Disputes: Can Statin Lipid-lowering Erapy Affect Cognitive Imentioning
confidence: 98%